Water-Energy Nexus in Saudi Arabia. (May 2017) - Rambo, Khulood A.; Warsinger, David M.; Shanbhogue, Santosh J.; V, John H. Lienhard; Ghoniem, Ahmed F.
Abstract: Water and energy systems have often been treated as separate "silo" systems over the entire pathway from production to consumption. However, their close interdependence requires some perspective of the water-energy nexus (WEN), especially in regions with very high water stresses combined with a myriad of rapid changes in resource production and consumption. This work provides a comprehensive analysis of the interdependence of water and energy in Saudi Arabia, including collecting data to map out energy and water consumption across the Kingdom. By combining and cross-referencing numerous data sources, this work creates the first country-wide Sankey diagram describing the interdependence of water and energy use in the Kingdom, and provides the most comprehensive mapping of power plant type and size. Additionally, this work reviews the energy and water industries, including outlining trends in population, urbanization, natural gas, oil, electricity, desalination, water use in energy production, and energy use in water production. Overall, a clear pattern has emerged: converging trends of rapid population increases, dwindling water resources, and rapidly growing desalination means that water use must be one of the primary driver of resource planning in Saudi, and plans to shift energy production to reduce GHG emissions must include water needs.